2015
DOI: 10.1007/s12663-015-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Association of Oral Submucous Fibrosis and Oral Squamous Cell Carcinoma and Incidence of Malignant Transformation of Oral Submucous Fibrosis in a Population of Central India: A Retrospective Study

Abstract: Aim To evaluate the incidence of oral squamous cell carcinoma concomitant with oral sub mucous fibrosis in central India and to correlate precipitating factors associated with oral submucous fibrosis and oral squamous cell carcinoma. This paper also aims to study the incidence of oral squamous cell carcinoma arising secondary to untreated oral submucous fibrosis. Materials and Methods Two hundred and twenty five cases of oral squamous cell carcinoma and one hundred and nineteen cases of oral submucous fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 13 publications
(19 reference statements)
4
42
1
Order By: Relevance
“…Primary malignancy of buccal mucosa and tongue was the most common site for OSCC‐OSMF compared to OSCC. These findings are in accordance with studies of VanWyk CW et al , Chourasia et al , and Muttagi et al . Betel quid being placed in close contact with buccal mucosa could be the reason for most common site in the OSCC‐OSMF group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Primary malignancy of buccal mucosa and tongue was the most common site for OSCC‐OSMF compared to OSCC. These findings are in accordance with studies of VanWyk CW et al , Chourasia et al , and Muttagi et al . Betel quid being placed in close contact with buccal mucosa could be the reason for most common site in the OSCC‐OSMF group.…”
Section: Discussionsupporting
confidence: 93%
“…Oral squamous cell carcinoma in the background of oral submucous fibrosis (OSCC‐OSMF) is one of the most common malignancies in South and South‐East Asian countries . In this regard, Chourasia et al reported 25.77% of OSCC‐OSMF. Recently, it has been proposed that OSCC‐OSMF constitutes a clinicopathologically distinct disease, the differences of which believed to arise from differential mechanisms of areca nut carcinogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…As OSMF malignant transformation is known to be independent of stage and site in the affected oral cavity ( Figure 1C), 23 For the first time to our knowledge, we analyzed bilateral buccal mucosa biopsies to further evaluate the uniformity of histological grade in multiple oral sites, finding grading agreement between bilateral biopsy sites was low (k = À0.478). This finding suggests there may be multiple grades of OSMF throughout the oral mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…As OSMF malignant transformation is known to be independent of stage and site in the affected oral cavity (Figure C), grouping OSMF patients with malignant transformation in late stages may result in losing vital data with prognostic value. Hence, the validity of any clinicopathological classification and its usefulness in treatment planning remains questionable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation